STRATEGI PROGRAM SIARAN RADIO DANGDUT DI JAKARTA (STUDI KASUS PADA KENAIKAN RATING RADIO MERSI FM TAHUN 2014) - . Liliyana (Jurnal Komunikasi, 2017)
As one of the dangdut’s radio station that have survived from 1970 until now, it isn’t easy for Radio Mersi 93,9 Jakarta. This tesis will analyze the success of program strategy that Radio Mersi has made to increase their rating.This is a descriptive study with a qualitative approached, using constructivis paradigm and using case study method. The data collection techniques through the observation, interviewed with the Radio Mersi programmer’s sources and literally data.The result showed that Radio Mersi has adjusted the program with its audience activities, formatting the listening habits which showed the same program every day, arranging the listeners’s flow which gave “the bridging” in each program, and optimizing the sound effect and music utilities to make more attractive. Unfortunately, Radio Mersi has lack of optimizing to maintaince the program’s resources which is seen by the repetition.Key words: Radio program strategy, Dangdut Radio in Jakarta